FOXC2 haploinsufficient mice are a model for human autosomal dominant lymphedema-distichiasis syndrome. - Kriederman, B; Myloyde, T; Witte, M; Dagenais, S; Witte, C; Rennels, M; Bernas, M; Lynch, M; Erickson, R; Caulder, MS; Miura, N; Jackson, D; et al. (2003)
Lymphedema-distichiasis (LD) (OMIM 153400) is a rare autosomal-dominant condition characterized by pubertal onset of lower limb lymphedema and an aberrant second row of eyelashes arising from the meibomian glands. In some patients cardiac, skeletal and other defects coexist. We previously identified inactivating, nonsense and frameshift mutations in the forkhead transcription factor FOXC2 in affected members of LD families. To further delineate the relationship of FOXC2 deficiency to the clinical (and lymphangiodysplastic) phenotype in this syndrome, we performed dynamic lymphatic imaging and immunohistochemical examination of lymphatic tissues in mice heterozygous (+/-) for a targeted disruption of Foxc2. Adult heterozygote mice characteristically exhibited a generalized lymphatic vessel and lymph node hyper plasia and rarely exhibited hindlimb swelling. Retrograde lymph flow through apparently incompetent interlymphangion valves into the mesenteric nodes, intestinal wall and liver was also observed. In addition, Foxc2 +/- mice uniformly displayed distichiasis. We conclude that Foxc2 haploinsufficient mice mimic closely the distinctive lymphatic and ocular phenotype of LD patients. Furthermore, the craniofacial, cardiovascular and skeletal abnormalities sometimes associated with LD have previously been shown to be fully penetrant in homozygous Foxc2 null mice. This Foxc2 mutant mouse thus provides an ideal model for exploring molecular mechanisms and physiologic events in mesenchymal differentiation associated with lymphatic growth and development and the clinical abnormalities seen in human LD syndrome.